A novel receiver design for HACO-OFDM by time-domain clipping noise elimination - Wang, Tao (2020)
The conventional receiver of hybrid asymmetrically clipped optical orthogonal frequency division multiplexing (HACO-OFDM) requires additional processing to regenerate and cancel the clipping noise, which increases the complexity of the receiver and makes the performance of pulse-amplitude-modulated discrete multitone (PAM-DMT) branch dependent on the accuracy of clipping noise estimation. In this work, a novel receiver of HACO-OFDM is proposed by fully exploiting the structure of time-domain signals. Through a time-domain processing, the clipping noise of the asymmetrically clipped optical OFDM (ACO-OFDM) can be removed and error propagation is avoided. Compared with the conventional receiver, the proposed receiver can achieve 58.3% complexity reduction in the case of a fast Fourier transform with size of 512. Simulation results show that the bit error rate (BER) of the proposed receiver is exactly the same as that of the conventional receiver for the ACO-OFDM branch, but when the clipping noise estimation in ACO-OFDM branch is inaccurate, the BER performance of the PAM-DMT branch is significantly improved over the conventional receiver.